Dampak Tata Kelola Perusahaan Dan Dewan Direksi Perempuan Terhadap Keberlangsungan Perusahaan: Sebuah Artikel Review - Maria Maranatha Gultom; Fajar Gustiawaty Dewi; Fitra Dharma (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2023)
This paper was written in response to an era of gender equality and inclusion, regulators, and society built an environment in which women entered workplaces that were previously considered male-dominated. In this era, the number of female employees at various levels of hierarchical organizations is increasing day by day, but when it comes to top-level managerial positions or participation on company boards, women's involvement is reported to be lacking worldwide. This research was established to determine whether female directors' composition has affected sustainability performance. This research found that according to several studies said that the Board of Directors of Women is more trustworthy than male colleagues in creating corporate sustainability, female directors do not want to be involved in matters of unethical behavior, such as earnings management. As women directors have theorized to be more risk-averse and conservative than their male counterparts, female directors are more concerned with their reputations. Female directors show more active collaboration and power-sharing in board meetings than male directors.